Phonetical features of portuguese language regional varients - E A Budnik (Russian journal of linguistics: Vestnik RUDN, 2009)
The article explains the features of consonant system of Portuguese language in African, Asian and Latin American countries, by using websites on English and Portuguese language. The transcription given on these websites is preserved in this article.